Effect of tribologically-induced changes in surface termination of silicon-containing diamond-like carbon coatings on the resistance to biomolecule adsorption. (31st October 2022) - Li, Zixuan; Ye, Jennings Z.; Yan, Jieming; Molina, Nicolás; Lien, Hsu-Ming; Chrostowksi, Robert; Jaye, Cherno; Fischer, Daniel A.; Lin, Jianliang; Mangolini, Filippo
Abstract: Silicon-containing diamond-like carbon (DLC) is a class of thin-film materials with excellent mechanical properties, high thermal stability, and good tribological performance over a wide range of environmental conditions. While non-alloyed/non-doped DLCs also exhibit good biocompatibility and bioinertness, our understanding of the effect of silicon in DLCs on biomolecules/DLC interactions is still elusive. Here, we evaluated the structural, mechanical, and tribological properties of Si-containing DLC coatings with silicon content fraction of 11% and 16%. Tribological tests, performed by sliding a stainless steel pin on the coatings in water, indicated a low friction response (steady-state coefficient of friction <0.11), while quartz crystal microbalance experiments indicated no adsorption of a model biomolecule, namely adenosine triphosphate (ATP), on Si-containing DLCs. Near-edge X-ray absorption fine structure spectromicroscopy analyses performed after tribological experiments provided evidence for an increase in the fraction of silanol surface terminal groups formed in the worn region upon sliding in water without any significant sp 3 -to-sp 2 rehybridization of carbon atoms. The fraction of surface hydroxyl groups in the worn region increases with the silicon content in Si-containing DLC, which leads to a decrease in friction. This tribologically-induced change in surface termination did not lead to the adsorption of ATP upon incubation of tribotested samples in ATP solutions for several hours. These findings open the path for the use of Si-containing DLC in applications requiring good tribological properties in aqueous solution and an excellent resistance to biomolecule surface adsorption that is maintained even after tribologically-induced variations in surface termination. Graphical abstract: Image 1 Highlights: Si-containing DLC coatings with [Si] fraction between 11% and 16% were grown. Increasing [Si] in DLC decreases friction in water. Sliding in water leads to an increase in silanol surface terminal groups. No adsorption of ATP occurs on Si-DLCs independently of the surface termination.